The Civil Society and Democracy Question: Politic, Economic and Socio-Cultural Democratization (UNWE Yearbook, 2014)
The main objective of thе paper is to outline the role of civil society in surmounting the democratic deficit in nowadays globalized neoliberal capitalism, the crisis of political representation and decline of the middle class. Through the prism of critical political theory, discursive and network approaches the concept of civil society is reconstructed, redefined (repleted with a new meaning) in the global era of transition from the modern to the postmodern public sphere in the direction towards political, economic and socio-cultural democratization. A special emphasis is placed on the activities of civil control, supervision and resistance against both the state (in cases of abuse of power, corruption, oligarchyzation, neo-authoritarianism) and capitalism and market failures (monopolies, oligopolies, cartels, etc., drastically undermining public interest and the sense of common good). The key for more democracy are the new forms of political participation and unconventional civic engagement in an atmosphere of publicity and constructive skepticism.The paper is structured in three parts: a) Civil society as an arena of democratization;  b) Civil society in-between the transition period  from liberal democracy to “post-democracy” c) The discourse of civil society in the Bulgarian transition. Based on the presented theories and concepts of civil society (on national, regional and global level) of different authors useful lessons are derived for Bulgaria – about on an analysis of the lamentable results of so-called “democratic transition” and on highlighting the positive perspective for the its democratic future .